Cortical Interlaminar Astrocytes Are Generated Prenatally, Mature Postnatally, and Express Unique Markers in Human and Nonhuman Primates. (15th September 2020) - Falcone, Carmen; Penna, Elisa; Hong, Tiffany; Tarantal, Alice F; Hof, Patrick R; Hopkins, William D; Sherwood, Chet C; Noctor, Stephen C; Martínez-Cerdeño, Verónica
Abstract: Interlaminar astrocytes (ILAs) are a subset of cortical astrocytes that reside in layer I, express GFAP, have a soma contacting the pia, and contain long interlaminar processes that extend through several cortical layers. We studied the prenatal and postnatal development of ILAs in three species of primates (rhesus macaque, chimpanzee, and human). We found that ILAs are generated prenatally likely from radial glial (RG) cells, that ILAs proliferate locally during gestation, and that ILAs extend interlaminar processes during postnatal stages of development. We showed that the density and morphological complexity of ILAs increase with age, and that ILAs express multiple markers that are expressed by RG cells (Pax6, Sox2, and Nestin), specific to inner and outer RG cells (Cryab and Hopx), and astrocyte markers (S100β, Aqp4, and GLAST) in prenatal stages and in adult. Finally, we demonstrated that rudimentary ILAs in mouse also express the RG markers Pax6, Sox2, and Nestin, but do not express S100β, Cryab, or Hopx, and that the density and morphological complexity of ILAs differ between primate species and mouse. Together these findings contribute new information on astrogenesis of this unique class of cells and suggest a lineal relationship between RG cells and ILAs.